BASLAWÍSH BILIMLENDIRIWDE MULTIMEDIA SABAQLARÍNÍŃ ÁHMIYETI - Kadrekova, A.; Maksetova, N. (SCIENCE and SOCIETY, 2022)
The article deals with information technologies in the system of continuous education, the use of multimedia in primary education, the use of information technologies in the process of the lesson.